Analyzing the Role of Mechanical Bowel Preparation on Surgical Outcomes in Colorectal Surgery: Role of Mechanical Bowel Preparation on Surgical Outcomes in Colorectal Surgery - Uzair, Muhammad; Afridi, Noor Sardar; Shah, Amjad Ali; Khan, Ayesha Ali; Khan, Ajmal; Zahir, Salman (Pakistan Journal of Health Sciences, 2024)
Despite improved postoperative recovery from the use of minimally invasive procedures and enhanced recovery after surgery protocols in recent decades, colectomy is still associated with morbidity. Surgical site infections range from trivial wound infections to potentially deadly colonic anastomotic leaks. Objectives: To compare the outcome results regarding postoperative complications of Mechanical Bowel Preparation and Non-Medical Bowel Preparation groups in elective colorectal surgery at a Tertiary Care Hospital in Peshawar, Pakistan. Methods: The research was a quasi-experimental study. In this study, 210 patients were included; they were divided into 2 groups: Mechanical Bowel Preparation Group and the Non-Mechanical Bowel Preparation Group. Data were collected through electronic health records. The data were analysed using SPSS software version 26.0. Descriptive statistics, such as the Chi-Square test, were applied to the results. Results: There was no statistically significant difference regarding the surgical outcomes and the demographics between the Mechanical Bowel Preparation and Mechanical Bowel Preparation groups. The escalation of the surgical site infection looked lower when the Mechanical Bowel Preparation was not in use i.e 20 (19.05%) in the Mechanical Bowel Preparation group and 14 (13.33%) in the Non-Mechanical Bowel Preparation group, but it did not seem to be, statistically significant; p-value=0.261014. The anastomotic leak rates and intra-abdominal collection rates do not differ significantly between the two groups; p>0.05. Conclusions: It was concluded that there was no statistical significance between the groups of mechanical bowel preparation and non-mechanical bowel preparation concerning surgical site infections, anastomotic leakages, and other colorectal surgery complications.